Infrastructural Commemorations: The Ground-Breaking Ceremony of the Third Bosphorus Bridge and the Endless “Conquest of Istanbul” - Laurent Dissard; İlknur Kurşunlugil (L'Espace Politique)
The ground-breaking ceremony of Istanbul’s Third Bosphorus Bridge took place on 29th May 2013. The date chosen by the then Prime Minister, Recep Tayyip Erdoğan, to launch the construction of this urban mega-project transformed the inauguration into a commemoration of the 560th anniversary of the Ottoman Conquest of Istanbul by Fatih Sultan Mehmet. After explaining the significance of the 29th May 1453 commemorations in Turkey, in this article, we argue that the building of mega-infrastructures, such as the Third Bosphorus Bridge, has become the occasion for Erdoğan to (re)conquer the city of Istanbul, thus mirroring Fatih Sultan Mehmet more than five centuries ago. In the end, we argue that the “Conquest Festival” in Istanbul today is perhaps more than just a celebration of the 15th century Ottoman siege of the city, but instead a diverted way for the nation to commemorate - without necessarily ever acknowledging it openly - the ethnic and religious “purification” of Turkey during the 20th century.